DEVELOPMENT OF AN ELECTRICAL SHRIMP TRAWL 1. REACTION OF SHRIMP TO LOW VOLT DIRECT CURRENT - NAMBOODIRI, K SREEDHARAN (Fishery Technology, 2025)
Preliminary attempts were made to assess the effect of directcurrent on shrimps and to see whether the shrimp could be guided inlarge numbers into the fishing net by using a current of appropriatevoltage without scattering them away as it happens at present. Thiscommunication is the first in the series of studies and primarily dealswith laboratory equipments and experimental procedures followed